Risk Management and First Aid Knowledge of Trekkers in Nepal - Lechner, K.; Scharfenberg, C.; Hettlich, E.M.; Giet, S.; Morrison, Audry; Schöffl, Volker; Küpper, Thomas (Health Promotion & Physical Activity, 2020)
Background: Trekking in Nepal is popular and generally safe. However preventable trekking injuries and deaths are often the result of poor risk managementand lack of skills – i.e. acute mountain sickness (AMS) and specific First Aid (FA). Shlim and Gallie’s reviews in 1992 and 2004 of trekking deaths here found a fivefold higher risk for fatal outcomes in organized trekking tours (OT) compared to independently organised trekkers (IT), including preventable deaths (i.e. AMS). Our survey sought to identify the AMS, FA and risk management knowledge/skills of OT and IT whilst trekking in Nepal. Methods: Based on previous pilot studies at the Khumbu region in Nepal, and on risk management information provided by leading German trekking operators, a survey was conducted using two questionnaires: one each for OT and IT.The study site was Manang (3,500m) in Annapurna region, Nepal. All trekkers passing through this site who volunteered their participation were included. For evaluation descriptive statistical methods and non-parametric tests were used. Results: 442 questionnaires were completed (155 OT; 287 IT). Mean agewas 36.4 +/– 12.0y and 61% were male. Mountaineering experience was low and FA training was scarce in both groups. IT (92.7%) followed acclimatization recommendations and 59.2% carried AMS medication, compared respectively to OT at 63.2% and 25.2%. Only 27.1% of OT had repatriation plans for a medical emergency. Conclusions: Most of OT and IT were inexperienced in mountaineering and in mountain emergencies. The preparedness of OT overall was inadequate and over-reliant on the organisers whose skills may also be inadequate when responding to an emergency. Responsible trekking should require that more than one person in a group have adequate, up-to-date riskassessment/management and FA skills specific to the trek, and in particular an understanding of altitude profile, AMS, and individual abilities.